2020
DOI: 10.1021/acsaem.0c00103
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene Stabilizer 4,11,15,30-Tetraarylamino Fullerenoarylaziridine: Regioselective Synthesis, Crystallographic Characterization Derivatives, and Potential Application as Propellant Stabilizer

Abstract: The safe storage of propellants has become increasingly challenging because of extreme storage and operational environments. Hence, high-performance stabilizers should be urgently developed to improve the stability of propellants. In consideration of the stability mechanism of stabilizers and the excellent free radical scavenging ability of fullerenes, we synthesized six fullerene stabilizers, 4,11,15,30-tetraarylamino fullerenoarylaziridines, through the nucleophilic substitution reaction of hexachlorofullere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Consequently, significant challenges have prompted the scientific community to seek effective alternatives. In this context, some other organic and inorganic chemical substances, such as fullerene-derivatives [1], phenols [11], lignin [12], triphenylamine (TPA), polymers, ketones, N-methyl-pnitroaniline derivatives, ionic liquids [13], natural products [14], zeolites [15], and malonanilides [16], have been tested as stabilizers for nitrate esters. Nevertheless, it is found that the replacement of the classical stabilizers with new compounds presenting less/no effect on the environment and human health is at the expense of the energetic material stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, significant challenges have prompted the scientific community to seek effective alternatives. In this context, some other organic and inorganic chemical substances, such as fullerene-derivatives [1], phenols [11], lignin [12], triphenylamine (TPA), polymers, ketones, N-methyl-pnitroaniline derivatives, ionic liquids [13], natural products [14], zeolites [15], and malonanilides [16], have been tested as stabilizers for nitrate esters. Nevertheless, it is found that the replacement of the classical stabilizers with new compounds presenting less/no effect on the environment and human health is at the expense of the energetic material stability.…”
Section: Introductionmentioning
confidence: 99%
“…Double base propellants (DBPs) are widely used for solid rocket motors and missile weapons owing to their high energy, wide range of burn rates, and low gas emissions [1]. DBPs are mainly composed of nitrate esters compounds [2].…”
Section: Introductionmentioning
confidence: 99%